Partnership dissolution: How does it affect income, employment and well-being? - Mike Brewer; Alita Nandi (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We assess comprehensively how incomes, employment, housing, mental health and life satisfaction change following a partnership dissolution, using data from 18 waves of BHPS. We confirm that women and children see living standards decline by more than men, on average, upon separation, but find that the fall in living standards is much greater for those women and children formally in high-income households; it is also high for older women with non-dependent children. We find that mental health and life satisfaction decline around separation, but both return quickly to pre-split levels at rates which are little related to post- split circumstances.
Keywords: I32; J12; K36; 330; British Household Panel Study; partnership dissolution; separation; divorce; GHQ; living standards; mental health